Recognition of prior learning - a research under ISEKI_Food 3 project - Rosa, Marco Dalla (2011)
In the frame of the ISEKI_Food 3 Erasmus Thematic Network activities, a working group related to the Life Long learning has been established. A questionnaire was created in order to know if and how the prior experiental learning (courses, working activities, language certifications, computer license, etc.) are considered and accreditated /recognised by the universities belonging the ISEKI_Food and ISEKI_Mundus partners to give academic credits to the students with prior certified experiences in order to facilitate the student's curriculum. Among the questions, data on a maximum of credits to be recognized, disciplines more frequently submitted to recognition, type of agreement between university and other institutions (secondary schools, training agencies, etc,), prior experience / learning, were included into the questionnaire. The recognition of priorlearning or experiences resulted to be mainly related to foreign language certification and working experience in non-academic environment as well as industries or analytical laboratories. Credits in informatic certification (i.e. European Computer Driving License) and demonstrated personal skills courses were also considered.